2020
DOI: 10.1088/1748-9326/ab7e4f
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in daily continental-scale atmospheric circulation biases between generations of global climate models: CMIP5 to CMIP6

Abstract: This study evaluates and compares historical simulations of daily sea-level pressure circulation types over 6 continental-scale regions (North America, South America, Europe, Africa, East Asia, and Australasia) by 15 pairs of global climate models from modeling centers that contributed to both Coupled Model Intercomparison Project Phase 5 (CMIP5) and CMIP6. Atmospheric circulation classifications are constructed using two different methodologies applied to two reanalyses. Substantial improvements in performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 39 publications
(40 reference statements)
4
38
0
Order By: Relevance
“…1 of this study and Anstey et al (2013) over the Euro-Atlantic sector. Increasing horizontal resolution may also result in an overall improvement in representing the synoptic-scale atmospheric circulation (Cannon 2020) and associated linkages between blocking and cold temperature extremes over the Pacific-North America. This study identifies blocking events using the meridional gradients of 500 hPa geopotential heights; however, this approach has difficulty detecting omega-shaped blocking events that often occur in the Pacific region, and different blocking methods have their own strengths and weaknesses (Woollings et al 2018).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…1 of this study and Anstey et al (2013) over the Euro-Atlantic sector. Increasing horizontal resolution may also result in an overall improvement in representing the synoptic-scale atmospheric circulation (Cannon 2020) and associated linkages between blocking and cold temperature extremes over the Pacific-North America. This study identifies blocking events using the meridional gradients of 500 hPa geopotential heights; however, this approach has difficulty detecting omega-shaped blocking events that often occur in the Pacific region, and different blocking methods have their own strengths and weaknesses (Woollings et al 2018).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Previous studies that analysed the performance capabilities of CMIP5 and CMIP6 GCMs have suggested that CMIP6 GCM represents an improvement over the previous versions (Song et al ., 2021; Wu et al ., 2019; Xin et al, 2020). In particular, Cannon (2020) evaluated simulations of daily sea‐level pressure circulation using the CMIP5 GCM and corresponding newer versions in CMIP6. As a result, it was found that the global error of the CMIP6 model was reduced by 24% compared with the previous version.…”
Section: Discussionmentioning
confidence: 99%
“…This can be done to investigate circulation biases in multi-model ensembles (e.g. Huth, 2000;Pastor and Casado, 2012;Stryhal and Huth, 2019;Cannon, 2020) as well as to identify possible changes in largescale circulation under future climate change scenarios (e.g. Belleflamme et al, 2013;Riediger and Gratzki, 2014).…”
Section: Introductionmentioning
confidence: 99%